Benthic foraminiferal assemblages and morphological abnormalities in the Subaé estuarine system, Bahia - Brazil - Burone, Leticia; Lessa, Guilherme; Machado, Altair; Figuêredo, Juzenilda (Anuário do Instituto de Geociências, 2006)
Abstract